ANALISIS PERBANDINGAN KINERJA KEUANGAN PDAM BANDARMASIH KOTA BANJARMASIN SEBELUM DAN SELAMA COVID-19 - Netty Nurhayati; Mega Andani (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research is to compare the financial performace of PDAM Bandarmasih in Banjarmasin city before and during the Covid-19 pandemic. The population of this research is PDAM Bandarmasih Financial Report. The sample is balance sheet and income statement from April to December 2019 for the period before covid-19 and April to December 2020 for the period during covid-19. Hypothesis testing using parametric test ‘Paired sample t-test’ and non parametric test ‘Wilcoxon Sign Test’. The Result of this study, state that the financial performance of PDAM Bandarmasih as measured by the Liquidity Ratio, Solvency Ratio and Basic Earning Power Ratio during Covid-19 is significantly different and better than before Covid-19.